CLINICOPATHOLOGICAL STUDY OF OVARIAN NEOPLASMS – AN INSTITUTIONAL PERSPECTIVE - GARDAS, VASUNDARA; CHERUKURI, PRASANTHI; SALOMI, SUMERA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to know the frequency and histomorphological patterns of ovarian neoplasms concerning age. Methods: A 2-year retrospective study was done in the pathology department, GITAM Institute of Medical Sciences and Research. Data were retrieved from laboratory records, H & E slides of ovarian biopsies of diagnosed neoplasms were screened. Results: During the study period, 70 ovarian neoplasms were reported. Ovarian tumors were categorized according to the WHO classification. In this study surface, epithelial tumors were most common at 87.14% followed by germ cell tumors at 11.42% and sex cord-stromal tumors at 1.42%. Serous cystadenoma was the most common benign surface epithelial tumor. Conclusion: Histopathology is the gold standard for diagnosing ovarian neoplasms. Newer diagnostic techniques such as immunohistochemistry and morphometric analysis help decide management and prognosis.